LSD acutely impairs working memory, executive functions, and cognitive flexibility, but not risk-based decision-making. Issue 13 (10th October 2020) - Pokorny, Thomas; Duerler, Patricia; Seifritz, Erich; Vollenweider, Franz X.; Preller, Katrin H.
Abstract: Background: Psychiatric and neurodegenerative illnesses are characterized by cognitive impairments, in particular deficits in working memory, decision-making, and executive functions including cognitive flexibility. However, the neuropharmacology of these cognitive functions is poorly understood. The serotonin (5-HT) 2A receptor might be a promising candidate for the modulation of cognitive processes. However, pharmacological studies investigating the role of this receptor system in humans are rare. Recent evidence demonstrates that the effects of Lysergic acid diethylamide (LSD) are mediated via agonistic action at the 5-HT2A receptor. Yet, the effects of LSD on specific cognitive domains using standardized neuropsychological test have not been studied. Methods: We examined the acute effects of LSD (100 µ g) alone and in combination with the 5-HT2A antagonist ketanserin (40 mg) on cognition, employing a double-blind, randomized, placebo-controlled, within-subject design in 25 healthy participants. Executive functions, cognitive flexibility, spatial working memory, and risk-based decision-making were examined by the Intra/Extra-Dimensional shift task (IED), Spatial Working Memory task (SWM), and Cambridge Gambling Task (CGT) of the Cambridge Neuropsychological Test Automated Battery. Results: Compared to placebo, LSD significantly impaired executive functions, cognitive flexibility, and working memory on the IED and SWM, but did not influence the quality of decision-making and risk taking on the CGT. Pretreatment with the 5-HT2A antagonist ketanserin normalized all LSD-induced cognitive deficits. Conclusions: The present findings highlight the role of the 5-HT2A receptor system in executive functions and working memory and suggest that specific 5-HT2A antagonists may be relevant for improving cognitive dysfunctions in psychiatric disorders.